Effect of Intermittent Fasting on Ureum in Hypertension Patients - Harahap, Huntari; Kusdiyah, Erny; Zami, Muh. Husni Zam (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Hypertension is a silent killer that causes 10.44 million people to die every year. The prevalence of hypertension based on the 2018 Riskesdas results has also increased, as well as in Jambi Province. In pre-clinical and clinical studies, intermittent fasting and physical activity are non-pharmacological therapies for hypertension and reducing risk factors for cardiovascular disease. This study aims to determine the effect of intermittent fasting and moderate physical activity on systolic blood pressure and creatinine in hypertension sufferers in Jambi City. Methods: This research is a quasi-experimental research with a cross-sectional research design. The research was conducted on 45 patients suffering from hypertension who received treatment at the Community Health Center in Jambi City, and did not suffer from heart disease, kidney failure, history of stroke or diabetes mellitus. The research sample had urea and creatinine checked before and after the study, carried out intermittent fasting twice a week for 1 month, and had their blood pressure measured once every three days. Respondents received guidance regarding moderate physical activity by providing exercise guidance and sports videos of moderate physical activity. Result: The results of the study showed that intermittent fasting and moderate physical activity in hypertensive patients can reduce systolic pressure, systolic blood pressure after intermittent fasting (mean=135.2+19, 9) compared to before (mean=144.1+21.1) (t-test; p=0.001) as well as reducing urea levels, after the intermittent fasting diet, the average creatinine level was 23.6 (11.9 - 65.7) compared to previously 20.4 ( 11 - 74) (t-test; p=0.001). Conclusion: The conclusion of this study is that intermittent fasting and moderate physical activity can reduce systolic blood pressure and urea in hypertensive sufferers.. .